Remote Work Dynamics: Managerial Challenges and the Test of Time in Human Resource Management - Perey Untajana, Paulus; Souisa, Novita; Kopong, Anthoneta (International Journal of Management Science and Information Technology, 2025)
Information and communication technology advances have influenced how various organizations function, particularly the remote work. Although offering flexibility, this form of work has raised few challenges in HR management. This study seeks to examine the obstacles faced by managers in supervising their remote and in office staff. This study utilizes a qualitative method that examines data obtained from literature and related materials. The results show that while firms realize financial gains in the form of cost savings and better performance, there is a distance between remote workers and office workers and a gap in between both of them, particularly in working conditions and resource accessibility. Remote workers are having the typical remote worker issues that are impacting their productivity, but office workers are feeling underrepresented and it’s difficult for them to fit into this new model. However, many HR managers are not sufficiently well prepared to face the new adversities, particularly in terms of training, motivation and communication. Thus, the present study implies the need for more integrative policies and better preparedness of managers to facilitate adjustment to these transitions.